Characterization and Strain Improvement of a Hypercellulytic Variant, Trichoderma reesei SN1, by Genetic Engineering for Optimized Cellulase Production in Biomass Conversion Improvement - Qian, Yuanchao; Zhong, Lixia; Hou, Yunhua; Qu, Yinbo; Zhong, Yaohua (Frontiers in Microbiology, 2016)
The filamentous fungus Trichoderma reesei is a widely used strain for cellulolytic enzyme production. A hypercellulolytic T. reesei variant SN1 was identified in this study and found to be different from the well-known cellulase producers QM9414 and RUT-C30. The cellulose-degrading enzymes of T. reesei SN1 show higher endoglucanase (EG) activity but lower β-glucosidase (BGL) activity than those of QM9414 and RUT-C30. A uracil auxotroph strain, SP4, was constructed by pyr4 deletion in SN1 to improve transformation efficiency. The BGL1-encoding gene bgl1 under the control of a modified cbh1 promoter was overexpressed in SP4. A transformant, SPB2, with four additional copies of bgl1 exhibited a 17.1-fold increase in BGL activity and a 30% increase in filter paper activity. Saccharification of corncob residues with crude enzyme showed that the glucose yield of SPB2 is 65% higher than that of SP4. These results reveal the feasibility of strain improvement through the development of an efficient genetic transformation platform to construct a balanced cellulase system for biomass conversion.